2003
DOI: 10.1152/ajpcell.00048.2003
|View full text |Cite
|
Sign up to set email alerts
|

VCAM-1-mediated Rac signaling controls endothelial cell-cell contacts and leukocyte transmigration

Abstract: Leukocyte adhesion is mediated totally and transendothelial migration partially by heterotypic interactions between the beta1- and beta2-integrins on the leukocytes and their ligands, Ig-like cell adhesion molecules (Ig-CAM), VCAM-1, and ICAM-1, on the endothelium. Both integrins and Ig-CAMs are known to have signaling capacities. In this study we analyzed the role of VCAM-1-mediated signaling in the control of endothelial cell-cell adhesion and leukocyte transendothelial migration. Antibody-mediated cross-lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
174
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(180 citation statements)
references
References 68 publications
4
174
0
1
Order By: Relevance
“…The ensuing cell retraction promotes gap formation and vascular permeability 52 . Previous studies have shown that antibody-mediated crosslinking of VCAM1 stimulated a Rac/ROS/p38 signalling cascade in endothelial cell during leukocyte transmigration 29 . Accordingly, we found that intracellular ROS production contributes to activation of p38 MAPK and MLC2 in endothelial cells stimulated by SPARC-competent melanoma secretome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ensuing cell retraction promotes gap formation and vascular permeability 52 . Previous studies have shown that antibody-mediated crosslinking of VCAM1 stimulated a Rac/ROS/p38 signalling cascade in endothelial cell during leukocyte transmigration 29 . Accordingly, we found that intracellular ROS production contributes to activation of p38 MAPK and MLC2 in endothelial cells stimulated by SPARC-competent melanoma secretome.…”
Section: Discussionmentioning
confidence: 99%
“…As VCAM1 has been shown to mediate endothelial junction disruption through Rac-dependent production of reactive oxygen species (ROS) and activation of p38 during leukocyte transmigration 29 , ROS levels were monitored in endothelial cells exposed to CM prepared from 1205Lu melanoma cells ( Supplementary Fig. 9e,f).…”
Section: Tumour-derived Sparc Induces Vascular Permeability In Vitromentioning
confidence: 99%
“…The mechanism by which ROS influences Fas clustering is unknown at present and requires investigation. Presumably, ROS activate signals that eventually result in cytoskeleton reorganization and membrane protein clustering van Wetering et al, 2002). We are in the progress of determining the exact cellular processes involved in cisplatin-mediated apoptosis, from ROS generation to Fas aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of the active Rac1 mutant V12Rac1 resulted in enhanced ROS production and loss of endothelial barrier integrity (427). Rac1 activation has also been demonstrated in trafficking of inflammatory cells across the endothelial barrier (428). Cross-linking of vascular cell adhesion molecule-1 (VCAM-1) on endothelial cell surface induced Rac1 activation and ROS generation, and resulted in loss of endothelial cell-cell adhesion and transendothelial leukocyte migration (428).…”
Section: A Nadph Oxidase-derived Ros In Inflammationmentioning
confidence: 99%